2011
DOI: 10.1364/oe.19.017402
|View full text |Cite
|
Sign up to set email alerts
|

Design of polarization-insensitive multi-electrode GRIN lens with a blue-phase liquid crystal

Abstract: We report the design and simulation results of an adaptive GRIN lens based on multi-electrode addressed blue phase liquid crystal. A high dielectric constant layer helps to smoothen out the horizontal electric field and reduce the operating voltage. Such a GRIN lens is insensitive to polarization while keeping parabolic phase profile as the focal length changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Polymer-stabilized blue phase liquid crystal (PS-BPLC) microlenses [28][29][30][31][32][33][34] have been developed with several attractive features: (1) submillisecond response time, (2) alignment-free, and (3) polarization insensitive. Blue phase [47][48][49][50] exists over a narrow temperature range (1-2 °C) between chiral nematic and isotropic phases.…”
Section: Operation Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymer-stabilized blue phase liquid crystal (PS-BPLC) microlenses [28][29][30][31][32][33][34] have been developed with several attractive features: (1) submillisecond response time, (2) alignment-free, and (3) polarization insensitive. Blue phase [47][48][49][50] exists over a narrow temperature range (1-2 °C) between chiral nematic and isotropic phases.…”
Section: Operation Principlesmentioning
confidence: 99%
“…To simplify the structure, Lee et al proposed a multi-electrode-structure PS-BPLC lens as shown in Figure 14 [32]. The bottom substrate has a planar electrode while the top glass substrate has multiple electrodes with different widths and different voltages.…”
Section: Ps-pblc Microlens With Multi-electrodementioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we demonstrate an alternative technique for realizing a gradual voltage drop, by using a layer with a high dielectric constant, ε. Although it is known that materials with high permittivity can be used as an alternative to resistive layers [13], to the best of our knowledge, this is the first report on the successful integration of liquid crystals with a ferroelectric thin film. Using the high permittivity of the ferroelectric thin film we demonstrate that a gradually varying potential between widely spaced electrodes can be obtained.…”
Section: Introductionmentioning
confidence: 96%
“…19 This is a phase that may be macroscopically considered as isotropic in the ground state, which, however, undergoes anisotropic refractive index changes when subjected to an external electrical field. In this case, the refractive index modifications may be similar for two orthogonal polarization components of light at normal incidence on the LC cell.…”
Section: Introductionmentioning
confidence: 99%